Factors predicting caregivers' readiness for vaccination of 5-11 years old children against SARS-CoV-2 - Saudi Arabia, 2022 - Al-Rasheedi, Ameinah Thamer; Elmuttalut, Mohammed Ahmed; AL-Mithn, Raghad Hamad; AL-Harbi, Ghaida Saleh; Al-Ghufaili, Ghadah Saleh; Al-Mohimeed, Yara Hamad; Al-Qutaymi, Anhar Ali; Al-Arfaj, Sarah Abdulrahman (The Journal of Infection in Developing Countries, 2022)
Introduction: A significant proportion of parents are still reluctant to have their children vaccinated against COVID-19. This study aimed to determine what factors influence parents' decision to get COVID-19 vaccine for the children of age group 5-11 years. Methodology: A cross-sectional study was conducted in the region Qassim of Saudi Arabia, by using a self-administered, pre-tested questionnaire to assess the predicting factors of caregivers’ readiness to get their children vaccinated against COVID-19. Results: Two-thirds of the caregivers surveyed were unwilling to get their children vaccinated against COVID-19. The factors that influence the parents’ decision to get their young children (5-11 years old) vaccinated against COVID-19 were: having secondary school education (p = 0.019), family members infected with SARS-CoV-2 (p = 0.016), caregivers completed the three doses of vaccination (p = 0.003) and those who received additional flu vaccine (p = 0.014), and not experiencing the side effects of COVID-19 vaccine (p = 0.0001). Additionally, no history of COVID-19 vaccine adverse events in older 12-18 year old children (p = 0.011) and no chronic diseases in the 5-11 year old children (p = 0.001) were predictors. Conclusions: Caregivers' preferences about the children’s vaccination were influenced by multiple factors, including educational level, having family members infected with SARS-CoV-2, caregivers completing three doses of COVID-19 vaccine, receiving additional flu vaccine with no or mild adverse events, and history of chronic diseases in the child. Understanding these factors can help determine the likelihood of the caregivers getting their child vaccinated.